BASIC SCHEME OF EDUCATION ADVOCATED BY MAHATMA GANDHI: THE APOSTLE OF PEACE - Zahida Jan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Mahatma Gandhi's Basic Scheme of Education, known as Nai Talim, is a holistic educational philosophy that integrates intellectual, physical, and moral development. Rooted in the socio-economic and cultural context of India, it emphasizes self-sufficiency, practical skills, and the dignity of labor. Central to this approach is the concept of "learning by doing," where productive crafts form the core of the curriculum, fostering self-reliance and economic independence. Gandhi advocated for education in the mother tongue, the inclusion of moral and ethical teachings, and the promotion of community living to instill values of cooperation and social responsibility. Despite challenges in implementation and adaptation to modern contexts, Gandhi's principles remain relevant, offering a model that balances academic learning with vocational training and character development. His vision underscores the importance of an education system that is inclusive, culturally rooted, and capable of producing well-rounded individuals who contribute positively to society. Revisiting Gandhi's Nai Talim can provide valuable insights for creating a more equitable and sustainable educational framework in contemporary times.